Pengembangan Jiwa Kewirausaha Melalui Kerajinan Kreatif Di Panti Asuhan Ummu Aiman - Jasri; M. Nur Taufiq; Nur Lita Sari; Rafikah; Nurfitriani; Sri Wulandari; Apriani; A. Rafni Tahir; Nurhikma Febryana Nirwan; Andi Miftahul Jannah; Dewi Nur Aisyah (CV. ITTC INDONESIA, 2025)
This community service activity was carried out at the Ummu Aiman Orphanage in Makassar City as an effort to cultivate an entrepreneurial spirit from an early age through creative craft training using recycled materials. This topic was chosen due to the limited availability of practical skill empowerment programs in orphanages that can support children's economic independence. The implementation methods included material presentations, demonstrations, hands-on practice, and participatory discussions using educational and communicative approaches. The children were guided to create simple products with both functional and economic value, such as pencil holders made from plastic bottles. The results showed that the participants became more active, confident, and capable of creating independently. In addition, their understanding of small business concepts and marketing through social media also began to form. This program had a positive impact on shaping independent, creative, and productive character. These findings serve as an important foundation for developing similar training models in other social institutions.